QUALITY IS AN EMANCIPATOR - Dewi Fatmasari (Universitas Pandanaran, 2016)
Talking about quality will definitely related to total quality management. TQM is a concept and method that requires the commitment and involvement of management and the entire organization in the management of the company to meet the desires or customer satisfaction consistently. So as to satisfy the desire or customer satisfaction, companies must sometimes break or against the habits that prevent and hinder in creating quality.Keyword : TQM, Quality, Emancipator